P09.09 PD-1 checkpoint blockade for treatment of mucormycosis and invasive aspergillosis in a stem cell transplant recipient. (1st October 2020) - Mueller, N; Banck, J; Mellinghoff, S; Schlösser, H; Thelen, M; Koehler, P; Schrötzlmair, F; Cornely, O; Lindner, LH; von Bergwelt-Baildon, M
Abstract : Background: Despite early surgical debridement and application of systemic antifungal drugs, invasive fungal infections by mucor spp. are still associated with a very poor prognosis in immunocompromised patients. Due to their lack of immune defense, targeted treatment strategies reversing the hyporesponsiveness of the immune system by immune checkpoints might improve patients' outcome. Until today, a successful recovery of mucormycosis after receiving anti-PD-1 antibody is only described once for a polytrauma patient. Therefore, we here describe the first immunosuppressed patient treated with nivolumab for invasive mucormycosis with aspergillus coinfection. Materials and Methods: A 51-year-old woman from Germany with acute myeloid leukemia (AML) relapse after allogenic hematopoietic stem cell transplantation was treated with azacitidine and lenalidomide. She acquired an invasive fungal infection with mucor species Lichtheimia ramosa combined with Aspergillus fumigatus in functional pancytopenia. Three surgical pansinusrevisions were performed and high dose i.v. antifungal treatment with liposomal amphotericin B and isavuconazole was initiated. Due to missing treatment response with daily mucor progression nivolumab 240 mg was administered and complemented by interferon γ (100µg s.c. 5 doses). Administration was repeated every 2 weeks (in total 4 doses of nivolumab, but only 10 doses of interferon γ due to recurrent fever episodes) and simultaneously i.v. antifungal treatment was deescalated. Blood samples were collected before (baseline treatment (BT)) as well as 2 weeks (under treatment (UT) 1) and 5 weeks (UT2) after treatment initiation with nivolumab. Peripheral blood mononuclear cells were isolated and flow cytometry analyses of lymphocytic subsets were performed. Results: Ten days after first dose of nivolumab, long-term local hemostasis was achieved. Local symptoms disappeared, sinusitis complaints improved, and inflammation values decreased significantly. Sixteen days after treatment initiation a CT scan revealed a partial remission of mucormycosis invasion. Follow-up CT scans showed a stable disease. Expression of PD-1 on T cells was monitored as proof of concept from BT on and showed a significant reduction from 34.7% to 3.3% (UT1) and 1.38% (UT2). Both activation markers CD86 and CD69 showed an increase from BT to UT1. T cells showed high maturation markers throughout monitoring, while B cell maturation increased from BT to UT1/2. Nine weeks after diagnosis and despite long-term neutropenia the patient was still clinically stable under nivolumab treatment and discharged with continued deescalated antimycotic treatment. A bone marrow biopsy revealed a further progression of AML relapse. After 3 weeks during follow-up mucormycosis was still clinically stable. Ten days later the patient developed fever up to 39.5°C, but refused to seek medical attention due to unfavorable prognosis of AML and died two days later from septic shock combined with disseminated intravascular coagulation. Conclusions: In immunocompromised hematological patients with invasive fungal infections, immune checkpoint inhibition is capable of reversing an infection-induced immunosuppressive phenotype. Therefore, it might complement the treatment of invasive fungal infections and should be evaluated in future clinical trials. Disclosure Information: N. Mueller: None. J. Banck: None. S. Mellinghoff: None. H. Schlösser: None. M. Thelen: None. P. Koehler: None. F. Schrötzlmair: None. O. Cornely: None. L.H. Lindner: None. M. von Bergwelt-Baildon: None.